2014
DOI: 10.4172/2161-119x.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hearing Loss among First Grade School Children in Tirana,Albania – A Repeated Cross-Sectional Survey

Abstract: Background: Hearing Loss (HL), which affects disproportionally children in low income countries, is increasing worldwide. HL could be associated with a range of speech, language and cognitive problems in children. In Albania the information about this condition is largely outdated. In this context, the aim of this paper was to assess the prevalence of HL among first grade school children in Tirana, the capital city of Albania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The prevalence of SNHL has been reported at 0.88% in Australian children in first through fifth grades, 2.05% in children in the United Kingdom ages 9–16 years, and 5.4% among school‐aged children in the United States . Among those with SCD, SNHL was found in 3.8%–30.9% of children in six pediatric studies .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SNHL has been reported at 0.88% in Australian children in first through fifth grades, 2.05% in children in the United Kingdom ages 9–16 years, and 5.4% among school‐aged children in the United States . Among those with SCD, SNHL was found in 3.8%–30.9% of children in six pediatric studies .…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to findings by Chishty et al [7] in Bemina, Yamamah et al [20] in Egypt and Absalan et al [31] in Iran. Sallavaci and colleagues [4], in Albania reported a lower prevalence of hearing loss of 4.4%. However, Skarzynski et al [32] in Poland, Obukowho et al [33] in Nigeria, Klas et al [34] in Brazil and Nogueira et al [35] all reported higher prevalence of hearing loss of 23.7%, 29.4%, 29.5% and 34.0% respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Al-Humaid et al [9] in Saudi and Chishty et al [15] in Bemina reported a similar finding of 7.5% and 6.5% respectively. Thakur et al [1] in Nepal, Adhikari et al [2] also in Nepal, Sallavaci et al [4] in Albania, Chandha et al [7] in India and Siddartha et al [10] also in India, all reported a lower prevalence of OME of 1.1%, 3.7%, 1.4%, 3.1% and 4.5% respectively. However, Yamamah et al [20] and Sharath et al [28] reported a higher prevalence of 10.8% and 13.3% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation